Chromatography The Most Versatile Method of Chemical Analysis - de Azevedo Calderon, Leonardo (IntechOpen, 2012)
Nowadays, Chromatography is the most versatile and widespread technique employed in modern chemical analysis and plays a vital role in the advancement of chemistry, biology, medicine and related fields of research. Because of the inherent simplicity and ease of operation, it can be used together with a wide range of detection systems, including electrochemical, photometric and mass spectrometry, being an invaluable laboratory tool for the separation and identification of compounds. The purpose of this book is not only to present the latest state and development tendencies of chromatography, but to bring the reader useful information on separation sciences to enable him to use chromatography on his research field. Taking into account the large amount of knowledge about chromatography theory and practice presented in the book, it has three major parts: applications, theory and sample preparation. The book is also intended for both graduate and postgraduate students in fields such as chemistry, biology, biotechnology, forensic, medicine, pharmacology and engineering, and as a reference for professionals and practitioners.